A Blockchain tool to detect and mitigate e-book piracy: a case study of Kenya - Nzangi, J. M. (Strathmore University, 2023)
Numerous online e-book markets have emerged along with the growth of e-book readers. This has also increased the speed and ease with which people share books. As a result, piracy has been skyrocketing since there is no security for books being shared, allowing only one person to have one copy of the purchased books. Globally, e-book piracy has been a significant setback for publishers, as the available solutions cannot offer the necessary content protection. A good example is the strict Digital Rights Management (DRM) that occasionally annoys real readers by preventing them from accessing their books or forcing them to forfeit ownership if the platform is shut down. Publishers, online platform providers, and writers currently comprise the e-book market. E-book piracy has real-world consequences that affect both publishers' and authors' bottom lines and their ability to produce more books. This work developed a non-fungible-token-based e- book platform that enables writers to self-publish e-books and sell them without the risk of piracy. NFTs, or non-fungible tokens, are digital assets that stand in for real-world things like artwork, collectibles, and game assets. New Financial Instruments (NFTs) use blockchain and smart contracts as their underlying digital infrastructure. When published, each book will have a separate non-fungible token (NFT) attached to it. The study used a trusted and secure e-book transaction system that meets the following security requirements: license verification for each e-book, content confidentiality, right to read authorization, authenticating a genuine buyer, confirming the validity and integrity of e-book contents, direct purchase safety, and preventing e-book piracy and illegal downloading. The developed solution will be a lifesaver for the e-book industry in Kenya and other regions worldwide since they offer an easy way for readers and authors to easily make secure e-book transactions with zero risk of piracy or denial of access for legitimate access users. Keywords: Blockchain, E-book, Non-Fungible Tokens, Piracy, Smart Contracts.
Full - text thesis